Jak ująć treści regionalne w edukacji? - Czarnik, Mirosław (Dydaktyka Polonistyczna, 2015)
This article aims to present the ways of including region-centered materials into secondary education. The author is concerned with overall educational goals and objectives which can be achievedthanks to regional education, most notably through the emotional connection created between astudent and their region of residence. According to the author, the most efficient method supporting this kind of education is the project method of teaching, which he discusses theoretically as wellas practically (The richness of variety. Multicultural history of Strzyzow region - project realised bystudents of Liceum Ogólnokształcące im. Adama Mickiewicza w Strzyżowie).